2014
DOI: 10.1002/etc.2550
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in Mississippi air and rain: A comparison between 1995 and 2007

Abstract: A variety of current-use pesticides were determined in weekly composite air and rain samples collected during the 1995 and 2007 growing seasons in the Mississippi Delta (MS, USA) agricultural region. Similar sampling and analytical methods allowed for direct comparison of results. Decreased overall pesticide use in 2007 relative to 1995 generally resulted in decreased detection frequencies in air and rain; observed concentration ranges were similar between years, however, even though the 1995 sampling site was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 43 publications
5
50
0
3
Order By: Relevance
“…These residues not only became ubiquitous or "pseudo-persistent" contaminants in surface water, in periods with increasing concentrations over the years (McKnight et al, 2015;Carvalho, 2017;Primost et al, 2017), but through surface waters they were shown to be able to reach the seas as well, as documented in Germany in the estuaries of the Baltic Sea (Skeff et al, 2015). Glyphosate and AMPA were also found at up to 2.5 and 0.48 µg/l in rain and up to 9.1 and 0.97 ng/m 3 in air, respectively in the USA in Mississippi, Iowa and Indiana States in 2004(Chang et al, 2011, where both have been identified in the same period as common surface water contaminants near agricultural fields (Majewski et al, 2014). Glyphosate and AMPA were detected both in rain and air near agricultural fields in the estuarine region of the Mississippi River in 2007, while such residues were not detected (possibly due to less sensitive analytical methods available at the time) in 1995 (Maqueda et al, 2017).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 60%
“…These residues not only became ubiquitous or "pseudo-persistent" contaminants in surface water, in periods with increasing concentrations over the years (McKnight et al, 2015;Carvalho, 2017;Primost et al, 2017), but through surface waters they were shown to be able to reach the seas as well, as documented in Germany in the estuaries of the Baltic Sea (Skeff et al, 2015). Glyphosate and AMPA were also found at up to 2.5 and 0.48 µg/l in rain and up to 9.1 and 0.97 ng/m 3 in air, respectively in the USA in Mississippi, Iowa and Indiana States in 2004(Chang et al, 2011, where both have been identified in the same period as common surface water contaminants near agricultural fields (Majewski et al, 2014). Glyphosate and AMPA were detected both in rain and air near agricultural fields in the estuarine region of the Mississippi River in 2007, while such residues were not detected (possibly due to less sensitive analytical methods available at the time) in 1995 (Maqueda et al, 2017).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 60%
“…The resulting atmospheric concentrations vary, and these currentuse pesticides have been detected hundreds of meters to kilometers away from application sites in both gas and particle phases (Coscollà et al, 2010(Coscollà et al, , 2008LeNoir et al, 1999). Atrazine, trifluralin, and metolachlor have been observed near application areas in concentrations ranging from < 1 ng m −3 to as high as 61 µg m −3 , and in urban and remote locations that are far from sources with concentrations < 2 ng m −3 (Foreman et al, 2000;Majewski et al, 2014;Peck A.M, 2005;Bedos et al, 2006;Coscollà et al, 2010).…”
Section: T Murschell Et Al: Gas-phase Pesticide Measurementmentioning
confidence: 99%
“…For detection of pesticides in the atmosphere, air samples are typically collected on solid-phase micro-extraction (SPME) fibers or other adsorbent materials with sampling times of 2 h-1 week (Bedos et al, 2006;Glotfelty et al, 1989;LeNoir et al, 1999;Majewski et al, 2014;Peck A.M, 2005). These solid adsorbents are analyzed by offline techniques, typically gas chromatography coupled to mass spectrometry (GC-MS) or electron capture detection (GC-ECD) (Bedos et al, 2006;Coscollà et al, 2010;Foreman et al, 2000;Glotfelty et al, 1989;LeNoir et al, 1999;Majewski et al, 2014;Peck A.M, 2005;Rice et al, 2002).…”
Section: T Murschell Et Al: Gas-phase Pesticide Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we believe we have identified a class of patients suffering from chronic kidney disease who statistically and collectively exhibit a profile of symptoms that can be explained as a consequence of chronic exposure to glyphosate in the ingested food and water. Our hypothesis is based, in part, on the increasing amounts of glyphosate found in food, air [3] [4], rain [3] [5], groundwater [5], surface water [4]- [6], soil [5], seawater [7], human serum [8] and urine [9], and even in samples of marijuana [10]. Formal testing of the suspected drugs and ingested foods for glyphosate contamination can and should be done to validate our hypothesis.…”
Section: Introductionmentioning
confidence: 99%